Intravenous ibuprofen in postoperative pain and fever management in adults: A systematic review and meta‐analysis of randomized controlled trials - Pengxiang Zhou; Lu Chen; Ente Wang; Lanzhi He; Shuxia Tian; Suodi Zhai (Wiley, 2023)
Abstract This study aims to evaluate the efficacy and safety of multiple or single‐dosage intravenous ibuprofen (IVIB) in managing postoperative pain and fever in adults who are unable to take oral medications. A systematic review and meta‐analysis was conducted based on randomized controlled trials (RCTs) comparing IVIB with placebo or other analgesic and antipyretic medications for postoperative pain and fever management. Data were collected from 8 main databases from the inception to June 2022. Risk of bias assessment was performed, and the GRADE methodology was used to assess the certainty of pooled evidence. Primary outcomes included visual analogue scale (VAS) scores within 24 h postoperative and reduction of temperature. Meta‐analyses were conducted to calculate the mean difference (MD) or risk ratios (RR) and 95% CIs. As a result, a total of twenty‐three RCTs with 3716 participants were included. For postoperative pain, with moderate‐to‐low certainty evidence, IVIB was associated with lower postoperative VAS scores than placebo, with MD ranging from −3.53 (95% CI, −4.32 to −2.75) at 0 min to −0.96 (95% CI, −1.35 to −0.57) at 24 h. Compared with intravenous acetaminophen, IVIB demonstrated lower VAS scores (MD, −1.54 at 0 min; −0.36 at 24 h). For fever, IVIB showed satisfactory antipyretic efficiency in a short period of time, but no difference was observed between IVIB and intravenous acetaminophen. IVIB was well‐tolerated for both pain and fever management. In conclusion, moderate‐to‐low certainty evidence supports the use of IVIB for adults with postoperative pain and fever who are unable to take oral medications.